A different type of influencer? Examining senior Instagram influencers communication - Miranda, Sandra (2022)
The aging of the population, the advance of ICT, and the opening of social networks have allowed the reception of massive phenomena led by the so-called digital immigrants. Indeed, despite the digital divide and a lesser predisposition of older people to deal with technology, it turns out that the market for senior digital influencers begins, gradually, to be marked by its growth, revealing specificities, and differentiating elements. This means that in addition to the traditional role of content receivers, older people are now active content creators, occupying a space that for a long time was restricted to younger generations, contributing to the building up of a vast audience and a wide range of interested, engaged and interactive followers. Using an exploratory approach, this research aims to study the Instagram profile of the top ten most popular elderly influencers and compare the posts of the top two digital influencers (man and women, each). For this purpose, a qualitative methodology was carried out, we examined and compared the posts of @Baddie Winkle, @Iris Apfel, @ George Takei and @dinneranddance, using several dimensions of analysis such as the topics covered, the tone of communication, and the audiovisual and multimedia resources used to create interaction and engagement with followers. The results show that fashion is one of the central themes, punctuated by a communication full of humor, fun, and eccentricity, challenging the paradigm and negative stereotype related to aging and breaking with the traditional image of decline, frailty, and disability associated with old age.